Database systems for advanced applications. DASFAA 2020 International Workshops : BDMS, SeCoP, BDQM, GDMA, and AIDE, Jeju, South Korea, September 24-27, 2020, Proceedings.: BDMS, SeCoP, BDQM, GDMA, and AIDE, Jeju, South Korea, September 24-27, 2020, Proceedings. ([2020]) - Unknown
No abstract available